Cerebral and cognitive modifications in retired professional soccer players: TC-FOOT protocol, a transverse analytical study. Issue 11 (9th November 2022) - Kepka, Sabrina; Lersy, François; Godet, Julien; Blanc, Frederic; Bilger, Mathias; Botzung, Anne; Kleitz, Catherine; Merignac, Jeanne; Ohrant, Emmanuel; Garnier, Franck; Pietra, François; Noblet, Vincent; et al.
Abstract : Introduction: Soccer is the most popular sport in the world. This contact sport carries the risk of exposure to repeated head impacts in the form of subconcussions, defined as minimal brain injuries following head impact, with no symptom of concussion. While it has been suggested that exposure to repetitive subconcussive events can result in long-term neurophysiological modifications, and the later development of chronic traumatic encephalopathy, the consequences of these repeated impacts remain controversial and largely unexplored in the context of soccer players. Methods and analysis: This is a prospective, single-centre, exposure/non-exposure, transverse study assessing the MRI and neuropsychological abnormalities in professional retired soccer players exposed to subconcussive impacts, compared with high-level athletes not exposed to head impacts. The primary outcome corresponds to the results of MRI by advanced MRI techniques (diffusion tensor, cerebral perfusion, functional MRI, cerebral volumetry and cortical thickness, spectroscopy, susceptibility imaging). Secondary outcomes are the results of the neuropsychological tests: number of errors and time to complete tests. We hypothesise that repeated subconcussive impacts could lead to morphological lesions and impact on soccer players' cognitive skills in the long term. Ethics and dissemination: Ethics approval has been obtained and the study was approved by the Comité de Protection des Personnes (CPP) No 2021-A01169-32. Study findings will be disseminated by publication in a high-impact international journal. Results will be presented at national and international imaging meetings. Trial registration number: NCT04903015 .